Comparison of two home-based polysomnography tools for OSAS diagnosis: a cost-minimization analysis. (20th October 2021) - Sapienza, M; Nurchis, M; Di Pumpo, M; Urbano, M; Hart, JG; Sommella, L; Pascucci, D; Riccardi, MT; Casale, M; Damiani, G
Abstract:  : Obstructive sleep apnoea syndrome (OSAS) is an underdiagnosed chronic disease with a high prevalence in adults. It is becoming an important social problem since it is associated with a significant adverse impact on quality of life and life expectancy. Overnight polysomnography, performed in a sleep laboratory (LabPSG), is considered the diagnostic standard. Home complete PSG (HoPSG) could represent an alternative to LabPSG for patients who want to avoid the overnight stay at a sleep center. The aim of this study was to assess the economic impact of two alternative HoPSG diagnostic techniques in the diagnosis of OSAS: the standard one versus the telemonitoring approach. The observational study was designed as a cost-minimization analysis adopting a healthcare perspective. The time horizon was 6 months (January 2021 - June 2021), thus no discounting was necessary. Direct medical costs, expressed in 2021 euros, were estimated through a micro-costing method while indirect costs were quantified adopting the Human Capital Approach. To explore the uncertainty of critical parameters, a one-way sensitivity analysis was run. Considering the direct costs, the telemonitoring HoPSG was estimated to cost around €55 less than the standard approach. The cost savings sharply increases taking into account the indirect costs that amounted to €90 million and €365 million for the telemonitoring and the standard approach, respectively. Sensitivity analyses results did not significantly differ from the base-case scenario. The diagnosis of OSAS is presently time-consuming, labor-intensive and costly. The adoption of digital health solutions as telemedicine has the potentiality to ease the diagnosis, to improve the access to health services, to reduce both direct and indirect costs, and to enhance the efficiency of healthcare facilities becoming a crucial tool in addressing the actual public health challenges. Key messages: The telemonitoring Home complete polysomnography is cost-saving compared with the standard approach. Telemedicine has the huge potential to overcome public health challenges as increases in chronic disease in an ageing society and the associated burden in healthcare costs.